Clinical Application of Progesterone for the Prevention of Preterm Birth, 2016 - Goodnight, William (American Journal of Perinatology, 2016)
While the preterm neonate continues to benefit from improved perinatal care, the rate of preterm birth in the United States remains significant. An increasing body of scientific literature has demonstrated the benefits of maternal progesterone administration in reducing primary and recurrent preterm birth. Intramuscular hydroxyprogesterone caproate is indicated in singleton pregnancies in women with a prior spontaneous preterm birth, while vaginal progesterone demonstrates similar efficacy in prolonging pregnancy in women with asymptomatic cervical shortening in the midtrimester. Given these favorable benefits, the use of progesterone has been expanded to other clinical situations at risk for preterm birth with less rigorous scientific evidence. This review highlights the current evidence-based clinical applications of progesterone for prevention of preterm birth.
Keywords: preterm birth; recurrent preterm birth; progesterone; vaginal progesterone; cervical shortening